Effects of work cessation on cognitive functioning in rural older adults in China: a cross-sectional study based on CHARLS - Xiao-hui Liu; Liang Zhu; Xiao-Yu Li; Wenwen Cheng; Ning-li Zhu; Jia-Xue Li; Sun Jing-Jing; Si-Yu Zhang; Dong-Guang Wang (BMJ Open)
Objectives This study investigated the effects of work cessation on cognitive function among older adults in rural China. Given that cognitive disorders affect 6.04% of individuals aged 60 and above—with higher prevalence in rural areas—understanding this relationship is critical.Design A cross-sectional study was employed, using data from the 2020 wave of the China Health and Retirement Longitudinal Study (CHARLS). Regression analysis assessed the impact of work cessation on cognitive function and the moderating effects of social activities, health behaviours and internet use.Setting Data were collected from 150 districts, 450 villages, and urban community units in China.Participants The study included 6,318 participants, with 4,045 currently employed and 2,273 no longer working.Main outcome measures Cognitive function was evaluated using measures of mathematical computation, temporal and image cognition, and situational memory was tested through 20 memory-related questions. Explanatory variables included work cessation status, while moderating variables encompassed social activities, health behaviours (smoking and alcohol consumption) and internet use.Results Work cessation has a negative impact on cognitive function, particularly situational memory and overall cognitive ability. Stopping work was associated with a decrease in cognitive functioning by 0.796 SD (p<0.01), a reduction in situational memory capacity by 1.083 SD (p<0.01) and a decline in total cognitive ability by 1.879 SD (p<0.01). However, more social activities, better health behaviours (eg, quitting smoking) and internet use can alleviate the impact. Seniors with high social activity levels showed an increase in cognitive functioning by 0.375 SD (p<0.01), while those who drank less alcohol had a 0.598 SD improvement in cognitive functioning (p<0.01). Internet use improved cognitive function by 1.265 SD (p<0.01).Conclusion Work cessation significantly reduced cognitive function in rural Chinese older adults. Leisure activities can mitigate this decline, but they often lack quality and diversity. Health behaviour improvements show heterogeneity, and internet use mitigates cognitive decline despite urban–rural digital gaps. To protect rural older adults’ cognitive function, policies promoting flexible employment, enhanced recreational infrastructure, health outreach and bridging digital divides are proposed.